Major factors that affects fertilizer sales performance at RBSB (M) Sdn Bhd / Siti Nur Afizan Abd Rahman - Abd Rahman, Siti Nur Afizan (2010)
Agriculture has always played an important role in the development of Malaysia and continues to make a major contribution to the national economy. Its gross domestic product (GDP) grew steadily from RM14.82 billion in 1990 to 40.07 billion in 2008. However the contribution of the agricultural sector reduces from 18.7% to 3.8% during the same period. This is caused due to the diversification and increase in other economic activities in the country. The Malaysian government has committed to promote and maintain agriculture as the third engine of growth in the country’s economy and this sector has maintained its GDP contribution at about 8.1% of an enlarged national GDP of RM738.67 billion in 2008. There are several factors that affect the fertilizers price in Malaysia such as the economy, climate and also the competition. These three factors can give the changes to the sales performance of the fertilizer company in Malaysia like RBSB (M) SDN BHD.